Health information technology implementation - Impacts and policy considerations: a comparison between Israel and Portugal - Catan, G. (2016)
The use of Information and Communications Technology (ICT) in health systems is increasing worldwide. While it is assumed that ICT holds great potential to make health services more efficient and grant patients more empowerment, research on these trends is at an early stage. Building on a study of the impact of ICT on physicians and patients in Israel, a Short Term Scientific Mission (STSM) sponsored by COST Net in conjunction with CIES/ISCTE IUL (Portugal) facilitated a comparison of ICT in health in Israel and Portugal. The comparison focused on patient empowerment, physician behavior and the role of government in implementing ICT. The research in both countries was qualitative in nature. In-depth interviews with the Ministry of Health (MOH), the private sector, patients associations, health plans and researchers were used to collect data. Purposeful sampling was used to select respondents, and secondary sources were used for triangulation. The findings indicate that respondents in both countries feel that patient empowerment has indeed been furthered by introduction of ICT. Regarding physicians, in both countries ICT is seen as providing more information that can be used in medical decision making. Increased access of patients to web-based medical information can strengthen the role of patients in decision making and improve the physician-patient relationship, but also shift the latter in ways that may require adjustments in physician orientation. Physician uptake of ICT in both countries involves overcoming certain barriers, such as resistance to change. At the national level, important differences were found between the two countries. While in Israel, ICT was promoted and adopted by the meso level of the health system, in particular the health plans and government intervention can be found in a later stage, in Portugal the government was the main developer and national strategies were built from the beginning. These two approaches present different advantages and disadvantages. Government involvement in earlier stages could provide benefit in terms of interoperability of systems between different healthcare organizations. However, innovation could be slowed down due to government bureaucracy or lack of leadership. The work provides information in order to understand and improve ICT services. Additionally, it provides input regarding impact of ICT on the physician/patient relationship and national policies in the area.